Strategi Inovatif Membangun Ketahanan Keuangan di Era Digital pada Perusahaan Netflix - Siti Ambar Mukti Puji Lestari; Maria Dinda Ayu Rosari Luruk Seran; Allesia Putri Wijaya Sutikno; Maria Yovita R Pandin (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Netflix is ​​an online film streaming service company that started from DVD rentals in 1999, and became a streaming application with a large surge in viewers during the Covid-19 pandemic. This research examines how Netflix can face financial resilience by presenting innovation. This research uses the ratio analysis method with the variables being tested for liquidity and profitability ratios, apart from that, this research also uses SWOT analysis. The research results analyzed include. from 2020 to 2022 it has a current ratio greater than 200%, which shows the company is not maximizing its use of asets. so it was repaired the following year. The company must increase the amount of liabilities so that asets experience a sufficient decrease. in 2020 to 2022 it has a quick ratio of almost close to 100% and in 2023 it experiences a decline which has an impact on the company.